Verbal encouragement improves game intensity, technical aspects, and psychological responses during soccer-specific training - Selmi, O.; Levitt, D. E.; Aydi, B.; Ferhi, W.; Bouassida, A. (International Journal of Sports Physiology and Performance, 2023)
Background: Soccer match outcomes rely on technical accuracy, intensity of play, and athlete motivation, and these parameters can be developed during sport-specific practice such as during small-sided games (SSGs). Verbal encouragement as a coaching technique improves exercise intensity and athlete enjoyment (indicative of motivation), but the impact on technical performance alongside these critical parameters remains unknown.